Description Of Family Support In The Care Of The Elderly With Hypertension In Penen Village, Sibiru-Biru District In 2022 - Indra Hizkia; Elsi Erisa Br Tarigan (Science Midwifery, 2022)
The elderly are often at risk of developing hypertension. This is because in the elderly they experience a decrease in the elasticity of the aortic wall, thickening of the heart valves, and a decreased ability to pump the heart. Thus, family support is needed by the elderly during the treatment period. The research purpose to determine the family support in the care of the elderly with hypertension in Penen Village, Sibiru–Biru District in 2022. The study used a descriptive method with a total sampling of 49 elderly respondents who had pre-hypertension and above (pre-hypertension, stage I, stage II). The results obtained description of family support based on good pre-hypertension are 14 respondents (93.3%) and 1 respondent in sufficient category (6.7%), family support based on stage I hypertension is good category 21 respondents (91.3% ) and sufficient category 2 respondents (8.7%), family support based on hypertension stage II in good category 2 respondents (18.2%), sufficient 8 respondents (72.2%) and less 1 respondent (9 ,1%). The conclusions from the research are mostly good family support. It is hoped that the family can provide more optimal support for the elderly to minimize and prevent complications of hypertension that occur in the elderly